Perbandingan Aktivitas Antimikroba Ekstrak Etanol dari Tiga Spesies Ganoderma Asal Pulau Lombok: Comparison of Antimicrobial Activities of Ethanol Extract from Three Species of Ganoderma Original Lombok Island - Faturrahman Faturrahman; Sukiman Sukiman; Bambang Fajar Suryadi; Sarkono Sarkono; Ernin Hidayati (LPPM Universitas Mataram, 2022)
The use of antibiotics is one of the most important ways to deal with the spread and treatment of pathogenic microbial infections. The search for new antibiotic sources continues to be carried out to anticipate the emergence of microbial resistance. One of the natural resources that has the potential as an antimicrobial source is a member of the macrofungi of the Genus Ganoderma. The purpose of this study was to evaluate the antimicrobial performance of the ethanol extracts of Ganoderma lucidum, G. applanatum dan Ganorderma sp. against fungi (Candida albicans dan Cryptococcus neoformans), gram positive bacteria (Bacillus cereus dan Staphylococcus aureus) and gram negative bacteria (Escherichia coli dan Shigella sp.). Macrofungi samples were taken from the forest area of Nature Tourism Park (TWA) Gunung Tunak, TWA Kerandangan, TWA Suranadi, TWA Nuraksa Sesaot, TWA Lemor and Pusuk forest. The stages of the method performed are sample collection, sample preparation, extraction, and testing of antimicrobial activity using the well difusion method. The ethanol extract concentrations for testing were 20%, 40%, 60% and 80%. The results showed that the three Ganoderma species had anti-fungal and antibacterial activity and that different levels of concentration had an effect on inhibition. The size of the inhibition zone is directly proportional to the higher the extract concentration. The antimicrobial activity of the ethanol extract of G. lucidum was higher when compared to G. applanatum and Ganoderma sp. both against fungi (Candida albicans and Cryptococcus neoformans) as well as against gram-positive and gram-negative test bacteria. In addition, G. applanatum showed very weak inhibition against both groups of tested bacteria. Key words: candidiasis; cryptococcosis; comorbid infections; macerations; pathogens